2017
DOI: 10.1021/acsami.7b00067
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Nitrogen Doping of Single-Layer Graphene Accompanied by Negligible Defect Generation for Integration into Hybrid Semiconductor Heterostructures

Abstract: While doping enables application-specific tailoring of graphene properties, it can also produce high defect densities that degrade the beneficial features. In this work, we report efficient nitrogen doping of ∼11 atom % without virtually inducing new structural defects in the initial, large-area, low defect, and transferred single-layer graphene. To shed light on this remarkable high-doping-low-disorder relationship, a unique experimental strategy consisting of analyzing the changes in doping, strain, and defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 62 publications
1
56
0
Order By: Relevance
“…The dashed lines indicate D, G and 2D peak positions of pristine graphene. (2020) 10:853 | https://doi.org/10.1038/s41598-019-55424-z www.nature.com/scientificreports www.nature.com/scientificreports/ a compressive strain and/or a modification of the carbon atoms in the graphene network by the incorporation of nitrogen atoms which could lead to an n-type doping 57 . Such blue-shifting peaks have been observed when an intentional plasma nitridation of graphene using either nitrogen 58 or ammonia 59 causes the introduction of defects as well as changes in the chemical and electronic properties of graphene.…”
Section: Resultsmentioning
confidence: 99%
“…The dashed lines indicate D, G and 2D peak positions of pristine graphene. (2020) 10:853 | https://doi.org/10.1038/s41598-019-55424-z www.nature.com/scientificreports www.nature.com/scientificreports/ a compressive strain and/or a modification of the carbon atoms in the graphene network by the incorporation of nitrogen atoms which could lead to an n-type doping 57 . Such blue-shifting peaks have been observed when an intentional plasma nitridation of graphene using either nitrogen 58 or ammonia 59 causes the introduction of defects as well as changes in the chemical and electronic properties of graphene.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 398.7 and 399.6 eV come from the nitrogen‐doped graphene and do not correlate with the underneath layer (see Figure S7a, Supporting Information). The peak at 398.7 eV is assigned to pyridine‐like N, corresponding to the sp 2 CN bonding configuration, while the peak at 399.6 eV indicates the presence of pyrroline‐like N corresponding to sp 3 CN . After the NH 3 pretreatment of graphene, both sp 2 CN and sp 3 CN are formed, as shown schematically in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, a blue shift is observed, which can be attributed mainly to the boron doping effect in graphene as the p-type. 8,25 G peak shifts of up to 8 and 10 cm À1 are observed for the films prepared using approaches 1 and 2 under the highest B flux, respectively. For the 2D peak, the corresponding values are 6.5 and 7.5 cm À1 , respectively.…”
Section: B)mentioning
confidence: 93%
“…Previous works have shown that the introduction of nitrogen dopants can open a bandgap in graphene 6,7 and also increase its carrier concentration. 8 Nitrogen and boron can induce ntype and p-type doping in graphene, respectively, but unintentional p-type doping can occur in pristine graphene due to species absorbed from the atmosphere such as oxygen and water vapor. 9 Since uncontrolled p-type doping is easily achieved in graphene, a higher research effort was devoted to nitrogen-doping in order to produce n-type graphene.…”
mentioning
confidence: 99%